2012
DOI: 10.1590/s1415-790x2012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Vacinação contra hepatite B e fatores associados entre cirurgiões-dentistas

Abstract: Objective: We calculated the prevalence and studied the factors associated with hepatitis B vaccination. Reasons for non-vaccination among dentists were investigated. Methods: A cross-sectional study was performed in Montes Claros, Minas Gerais, from 2007 to 2008, to assess hepatitis B vaccination among practicing dental surgeons. Variables were evaluated using a previously tested structured questionnaire. Data underwent descriptive analysis. Non-conditional logistic regression was used to determine the variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
(45 reference statements)
2
11
0
3
Order By: Relevance
“…The reported vaccination was also lower compared to other studies conducted in Brazil, among Primary Health Care workers, which obtained rates of 93.2% in Divinópolis-MG (11) , 64.6% in Florianópolis-SC (5) and other 76.2% in Mato Grosso do Sul (12) . The prevalence among these FHS workers (52.5%) could be even worse if dental surgeons were excluded, since a study with these professionals (dentists) of Montes Claros, who are probably included in the study population in question, reached a value of 91.2% (10) . Studies have shown resistance of health professionals regarding vaccination (7,13) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The reported vaccination was also lower compared to other studies conducted in Brazil, among Primary Health Care workers, which obtained rates of 93.2% in Divinópolis-MG (11) , 64.6% in Florianópolis-SC (5) and other 76.2% in Mato Grosso do Sul (12) . The prevalence among these FHS workers (52.5%) could be even worse if dental surgeons were excluded, since a study with these professionals (dentists) of Montes Claros, who are probably included in the study population in question, reached a value of 91.2% (10) . Studies have shown resistance of health professionals regarding vaccination (7,13) .…”
Section: Discussionmentioning
confidence: 98%
“…It is also relevant, since reported vaccination was lower compared to a study among dentists in the same city (Montes Claros-MG), which found that 91.2% reported Rev Bras Enferm. 2015 jan-fev;68(1):77-84. vaccination in 2008 (10) . The reported vaccination was also lower compared to other studies conducted in Brazil, among Primary Health Care workers, which obtained rates of 93.2% in Divinópolis-MG (11) , 64.6% in Florianópolis-SC (5) and other 76.2% in Mato Grosso do Sul (12) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the validity of the data collected by inspecting the vaccination cards and laboratory exam reports allowed adhesion to the vaccination measures to be known, without the possibility of response and memory biases resulting from the use of self-applicable questionnaires, because this was a documentary research. In the majority of studies in the literature, the data result from self-applicable questionnaires that depend on the participant's memory 1,5,[14][15][18][19][20] . In practice, it was only possible to carry out this inspection due to the dental school's demand that students had to hand in a copy of their vaccination card and anti-HBs exam result to the undergraduate course secretariat, so that these could be evaluated, and later attached to the documents of each student.…”
Section: Discussionmentioning
confidence: 99%
“…In teaching institutions, pedagogical efforts accompanied by continuous education must motivate students to use standard precautions correctly and routinely 6,15 . Vaccination against HBV is the measure for primary prevention and control of the disease, and so is the need for confirming seroconversion of the vaccinated persons 5,10,13 , thus emphasizing the importance of the demand by HLIs for students to present their vaccination card and seroconversion test results, thereby minimizing the risk in the case of an eventual exposure to infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation